On multipurpose control systems synthesis for non-square discrete-time multivariable plants - Bańka, Stanisław (Zielona Góra: Uniwersytet Zielonogórski)
Two cases of control systems are considered assuming that the state vector of the plant is either accessible or inaccessible for direct measurement. In the case of inaccessible plant's state vector, a stationary Kalman filter or a Luenberger observer is applied to estimate (to reconstruct) the state vector of the plant, which is then used in a linear state variable feedback.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka